Phenetic Relationships of Ferns Based on Morphological Characteristics in an Oil Palm Plantation of Tampaure Hamlet - Tiara Tiara; Lestari M.P Alibasyah; Yulia Windarsih; Musdalifah Nurdin; Manap Trianto; Vita Indri Febriani (Biology, Medicine, & Natural Product Chemistry, 2026)
Ferns (Pteridophyta) are a group of vascular plants that reproduce by spores and possess true roots, stems, and leaves, as well as xylem and phloem tissues. This study was conducted to investigate the phenetic relationships among fern species based on their morphological characteristics in an oil palm plantation located in Tampaure Hamlet, Bambaira District, Pasangkayu Regency, West Sulawesi, Indonesia. A field exploration method was employed, and samples were collected using a free-collection technique. Morphological data were compiled using Microsoft Excel and subsequently analyzed through Principal Component Analysis (PCA) and the Unweighted Pair Group Method with Arithmetic Mean (UPGMA) in PAST version 4.03. A total of 50 individuals representing 10 fern species were identified from both terrestrial and epiphytic habitats, namely Sphaerostephanos heterocarpus, Diplazium dilatatum, Davallia denticulata, Asplenium nidus, Selaginella delicatula, Pityrogramma calomelanos, Stenochlaena palustris, Lygodium circinatum, Nephrolepis biserrata, and Pteris wallichiana. The UPGMA analysis revealed that Pteris wallichiana and Sphaerostephanos heterocarpus exhibited the closest phenetic relationship, with a similarity index of 0.88. In contrast, the most distant relationship was observed between Selaginella delicatula and Asplenium nidus, with a similarity index of 0.63. The PCA biplot analysis demonstrated that the major variation distinguishing fern species in the study area was primarily influenced by meristic traits, particularly the number of fertile pinnae, as well as overall plant size. These morphological characteristics contributed substantially to species differentiation and the phenetic grouping pattern observed among the investigated fern species.